2018
DOI: 10.1007/s10549-018-4962-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic findings in reduction mammoplasty specimens: a surrogate for the population prevalence of breast cancer and high-risk lesions

Abstract: The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
5
17
0
Order By: Relevance
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the rate of AMBL in patients with no history of breast cancer was 3.3%. The previous studies that included only patients with no history of breast cancer reported the rate of AMBL to be between 1.5 and 14% 5,7–26 . The wide range of reported rates of AMBL in different studies can be attributed to different pathological assessment methods of RM specimens between institutions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated that NLP models can achieve high performance in parsing both English and Chinese pathology reports . We used this system to identify sets of specific characteristics that helped us to quantify the risk and efficacy of chemoprevention in women with atypical breast lesions and to identify atypical breast lesions and cancers among patients who underwent mammoplasty . Others have applied NLP techniques to parse breast image reports .…”
Section: Implementations Of Nlp In Clinical Genetics and Breast Cancementioning
confidence: 99%
“…Frame Elements References CANCER DIAGNOSIS NAME: cancer type [44], [45], [42], [46], [47], [48], [49], [50], [51] ANATOMICAL SITE: the location description of the finding (including primary and metastatic sites) [45], [52], [42], [53], [54], [55], [25], [27], [56], [57] HISTOLOGY: histological description (e.g. carcinoma) [44], [52], [58], [55], [53], [54], [4], [27], [59], [43], [57] GRADE: appearance of the cancerous cells, can be frame with further information (GRADING VALUE) [44], [52], [54], [4], [48], [27], [59], [60], [43], [61], [62] INVASION TYPE: the stage or level of invasion [52] TUMOR BLOCK: tissue cores removed from regions of interest in paraffinembedded tissues (e.g.…”
Section: Framementioning
confidence: 99%